PISANG SEBAGAI INSPIRASI DALAM KARYA RELIEF KAYU - Fathin Afif, Drs. Efrizal, M.Pd., Drs. Irwan, M.Sn. (Serupa The Journal of Art Education, 2018)
The purpouse of the final work creation is to visualize and express the admiration, interest, and author aesthetic experience on the beauty /aesthetics from banana plantation based from Qoran Chapter Al Waqiah verse 29, through wood carving. The method of creating artworks uses five stages: preparation stage, elaboration stage, synthesis stage, concept realization stage, and completion stage holding a final work wood carving exhibition. Wood carving used carved techniques. This art work illustrated anxiaty lack of interest from moslem society to read the holy Qoran, illustrated the life from born to die, and visualized the banana plantation.Kata kunci : Pisang, Inspirasi, Relief Kayu